Heads I Win, Tails You Lose: CEO Stock Options and Bank Performance during the Financial Crisis - Tjong, Peter (2010)
In the wake of the 2008 Financial Crisis a significant amount of attention has been focused on the compensation practices of the financial sector. Due to their asymmetric payoff it has been argued that stock options created incentives for bank CEOs to pursue excessively risky strategies that resulted in the crisis. This paper investigates whether CEO stock options influenced US bank performance during the Financial Crisis. No evidence is found that either CEO stock options or fixed salaries had a significant impact on bank share price performance during this period. This paper then moves on to review the regulation of executive compensation for TARP recipients in the US, discussing the shortcomings of these proposals and providing several alternative suggestions.